Structural Transitions in Ribonucleic Acid During Ribosome Development - Sypherd, Paul S. (1967)
Amino acid deprivation of a “relaxed” auxotroph of Escherichia coli results in the accumulation of protein-deficient, immature ribosomes (“relaxed particles”). The ribonucleic acid (RNA) of these particles was shown to differ from mature ribosomal RNA in both sedimentation characteristics and in elution from columns of methylated albumin-keiselguhr. When relaxed particles were allowed to become converted to mature ribosomes, the unique properties of the RNA were lost, and this RNA became indistinguishable from mature RNA. The conversion of relaxed particles to ribosomes did not involve degradation and resynthesis of RNA. It is concluded that ribosomal RNA undergoes a configurational transition during ribosome development, and that this transition is not the result of changes in the primary structure of the RNA.